2012
DOI: 10.1111/j.1600-0560.2011.01860.x
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen‐induced eccrine squamous syringometaplasia

Abstract: A 74-year-old woman had carcinoma of her right breast for which surgery was performed. Four weeks following the start of tamoxifen therapy, she developed papules and plaques over her face, trunk and limbs. A skin biopsy showed perivascular and periadnexal mixed inflammatory cellular infiltrate with fibroplasia. Notably, the dermis also showed squamous epithelial islands, which in foci were noted to be closely associated with eccrine epithelium. This was confirmed with double peroxidase - alkaline phosphatase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…6 Bilateral lesions associated with various medications such as nonsteroidal anti-inflammatory and chemotherapeutic drugs (doxorubicin, tamoxifen) have been reported that exhibit syringoma-like features, occasionally exhibiting squamous metaplasia of eccrine and apocrine sweat ducts and mucinproducing glandular cells. [7][8][9] Similar lesions have been reported in association with chronic radiation dermatitis. Idiopathic cases are rare but have been documented.…”
Section: Reactive Lesions/syringometaplasiassupporting
confidence: 73%
“…6 Bilateral lesions associated with various medications such as nonsteroidal anti-inflammatory and chemotherapeutic drugs (doxorubicin, tamoxifen) have been reported that exhibit syringoma-like features, occasionally exhibiting squamous metaplasia of eccrine and apocrine sweat ducts and mucinproducing glandular cells. [7][8][9] Similar lesions have been reported in association with chronic radiation dermatitis. Idiopathic cases are rare but have been documented.…”
Section: Reactive Lesions/syringometaplasiassupporting
confidence: 73%
“…Tamoxifen is known to be associated with a range of dermatological side effects including erythema multiforme, Stevens-Johnson syndrome, urticaria, vasculitis and eccrine squamous syringometaplasia. 13 It is of interest that the eccrine poromas in our patient were ER negative. Whether Tamoxifen has a role in stimulating the development of the eccrine poromas in our patient who continues on this medication and continues to develop widespread lesions is uncertain.…”
Section: Discussionmentioning
confidence: 72%
“…Apart from its uses in breast cancer, it can be used to treat infertility in women with anovulatory disorders. Tamoxifen is known to be associated with a range of dermatological side effects including erythema multiforme, Stevens‐Johnson syndrome, urticaria, vasculitis and eccrine squamous syringometaplasia . It is of interest that the eccrine poromas in our patient were ER negative.…”
Section: Discussionmentioning
confidence: 82%
“…In total, 21 cases, including the present patient, were identified. Vasculitis was the most common reported adverse cutaneous event for both tamoxifen and aromatase inhibitors, with four cases of vasculitis reported for both drug classes Other reactions to tamoxifen included subacute cutaneous lupus erythematosus (SCLE), radiation recall dermatitis, eccrine squamous syringometaplasia and a maculopapular eruption . Of the five cases involving anastrozole, three cases presented with vasculitis (including our patient) and one case each with SCLE and a micropapular eruption .…”
Section: Published Case Reports Of Cutaneous Adverse Effects Of Hormomentioning
confidence: 78%